A novel minimally invasive broken nail extractor for cannulated intramedullary nails: Trial and application in a few cases. Issue 46 (18th November 2022) - Zhou, Zihong; Jiang, Yan; Dai, Beichen; Mao, Guoshu; Liu, Yu; Wei, Changbao; Lin, Weidong
Abstract : Successful and minimally invasive extraction of a broken distal end of an intramedullary nail is challenging. This study introduces a simple and reproducible technique for the extraction of broken cannulated intramedullary nails using a novel minimally invasive broken nail extractor. Five amputated adult lower-leg specimens were used to create models of the broken distal end of the cannulated intramedullary nails remaining in the medullary cavity of the distal tibia. Two orthopedic resident physicians with experience in tibial intramedullary nail implantation were selected to blindly extract the broken intramedullary nail using the novel minimally invasive broken nail extractor. The extraction outcome was assessed. The broken nail extractor was applied to 3 patients with broken intramedullary nails remaining in the medullary cavity of the distal tibia. In the lower-leg specimens, the extraction success rate was 100%, the median number of extraction times was 1.9 (range 1–3.5), and the median duration of extraction was 38 s (range 20–52 s). All the broken intramedullary nails in the 3 patients were successfully extracted without complications related to the surgery. The study shows that our technique is simple, reproducible, and has a high extraction success rate, but more case applications are needed to verify its effect.